Penanganan Masalah Kesulitan Belajar Akademik - Habsy, Bakhrudin All; Senja, Agesti Tria Fatma; Mahmudah, Nur; Kartikasari, Dea Dwi (Lembaga Yasin AlSys, 2024)
This research aims to find out the types or obstacles that occur to students in carrying out the learning process and show how to overcome them. In this study we used the library research method. Learning difficulties are one of the conditions in which learners cannot achieve the expected learning objectives. This is caused by a gap between intelligence and academic abilities such as dyslexia, dyscalculia and dysgraphia. Dyslexia is a condition where children experience obstacles in processing writing into spoken language in the form of a combination of abilities and difficulties that affect the learning process in one or more skills such as reading, spelling, and writing. Dyscalculia is a condition where children have difficulty in the most basic mathematical calculations in mathematical arithmetic operations. While Dysgraphia is a condition where children experience obstacles or difficulties in the process of expressing thoughts in written composition in terms of grammar (syntax), word meaning, and the ability to decompose words into their sound components or unite sounds into words (phonology). Identifying forms of learning difficulties needs to be done early if we already see something that is not in accordance with the child's development. With this, it is hoped that these difficulties can be overcome properly by experts.